A Three‐Component Enantioselective Cyclization Reaction Catalyzed by an Unnatural Amino Acid Derivative. Issue 3 (12th December 2017) - de Gracia Retamosa, María; Ruiz‐Olalla, Andrea; Bello, Tamara; de Cózar, Abel; Cossío, Fernando P.
Abstract: A new diastereo‐ and enantioselective three‐component cyclization reaction is described. The reaction takes place between a ketone, a carboxylic acid, and a nitroalkene to yield a bicyclic octahydro‐2 H ‐indol‐2‐one scaffold possessing three chiral centers. This reaction involves a rearrangement of the nitro group under simple thermal conditions. A plausible mechanism is proposed for this new reaction based on DFT calculations and isotope‐labeling experiments. A new concise enantioselective synthesis of the alkaloid (+)‐pancracine is presented as an example of the potential of this novel organocatalytic cyclization reaction in the synthesis of natural products. Abstract : Brand new cycle : The unnatural and densely substitutedl ‐proline esterXL catalyzes the formation of bicyclic γ‐lactams possessing three new chiral centers. This new reaction has no equivalent in organocatalytic, enzymatic, or organometallic chemistry and can be used in the synthesis of complex natural products.